2017
DOI: 10.1080/13561820.2017.1340875
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an interprofessional communication and collaboration intervention to improve care capacity for heart failure management in long-term care

Abstract: Heart failure affects up to 20% of nursing home residents and is associated with high morbidity, mortality, and transfers to acute care. A major barrier to heart failure management in nursing home settings is limited interprofessional communication. Guideline-based heart failure management programs in nursing homes can reduce hospitalisation rates, though sustainability is limited when interprofessional communication is not addressed. A pilot intervention, 'Enhancing Knowledge and Interprofessional Care for He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Consistent with previous studies, students expressed an increase in their own understanding of interprofessional collaboration, improved communication, and support of one another as they now start to understand the convergence of their roles in the bigger picture of patient care. [10,11] Students in this study stated their desire to continue using IPS and suggested increasing access to this strategy in the educational curriculum. The theme, early implementation, established that students comprehend collaborative simulation as a valuable learning tool to foster confidence in their roles as nurses and social workers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Consistent with previous studies, students expressed an increase in their own understanding of interprofessional collaboration, improved communication, and support of one another as they now start to understand the convergence of their roles in the bigger picture of patient care. [10,11] Students in this study stated their desire to continue using IPS and suggested increasing access to this strategy in the educational curriculum. The theme, early implementation, established that students comprehend collaborative simulation as a valuable learning tool to foster confidence in their roles as nurses and social workers.…”
Section: Discussionmentioning
confidence: 83%
“…[4,8,9] Interprofessional practice is a key component for effective communication, improving patient care, increasing understanding between professions, reducing fragmented care, and improving patient safety. [5,[10][11][12][13][14][15] Inclusion of simulation enhanced interprofessional education (IPE) or interprofessional simulation (IPS) can allow health professionals to see the health care team's collaborative impact on patient care. [7,16] In the clinical setting, health care professionals are expected to work in teams, yet, there is limited academic exposure to other allied health students and little preparation is done in traditional classrooms to practice with other allied health students; a gap in curriculum that supports an interprofessional approach exists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45] There are a variety of tools and processes that may be helpful in developing more structured procedures for pamphlet distribution and follow up. For example, the Palliative Performance Scale which is a scale developed to identify when patients may benefit from endof -life care, or the 'surprise question' which prompts staff to use their clinical judgment to identify residents who could foreseeably die within a particular time frame, could be used to identify residents and families who would benefit from receiving a pamphlet [46][47] . Both of these triggers can be reliably used by care aides and support staff in LTC.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of a qualitative descriptive study explored the impact of introducing an initiative to increase interprofessional communication among healthcare professionals working with patients with heart failure. After introducing strategies to enhance communication, professionals felt they had greater knowledge of heart failure, and felt patients had improved clinical outcomes 33. While the importance of interprofessional communication within an outpatient service is evident, further research is needed to address how to optimise communication along the healthcare continuum, particularly with episodic illness where the continuum may not always be predictable, nor linear in nature.…”
Section: Discussionmentioning
confidence: 99%